Pengaturan Penjualan Minuman Beralkohol di Kota Medan Menurut Peraturan Perundang-Undangan yang Berlaku di Indonesia Dan Agama Islam - Tri Afandy; Mirza Nasution; Jelly Leviza (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The circulation of alcoholic beverages requires licensing, as regulated in the following regulations: Presidential Regulation of the Republic of Indonesia Number 74 of 2013 on the Control and Supervision of Alcoholic Beverages, and the Minister of Trade Regulation Number 20/M-DAG/PER/4/2014 on the Control and Supervision of Procurement, Distribution, and Sale of Alcoholic Beverages (hereinafter abbreviated as Minister of Trade Regulation No. 20/M-DAG/PER/4/2014) along with the amendments made by the Ministry of Trade. This study uses normative legal research because in addressing the formulated problems, it is clear that the research prioritizes literature or secondary data. Normative legal research emphasizes secondary data, including regulations and legal theories, while also examining the legal norms prevailing in society, leading to the discovery of legal principles in the form of dogma or legal doctrine that are scientifically theoretical and can be used to analyze the discussed issues. The regulation of alcoholic beverage sales is normatively adequate in the implementation of control over the sale of alcoholic beverages. According to the prevailing laws and regulations, the sale of alcoholic beverages is only permitted in certain places such as bars, discotheques, 3 to 5-star hotels, and locations that are not adjacent to places of worship, government offices, and hospitals. However, in reality, the practice of selling alcoholic beverages in the city of Medan still occurs in places that do not comply with the regulations, such as shops and wholesalers, resulting in legal uncertainty.